Grammatical Errors in English Study Made by UIB Students - Hartanto, Bobby (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2022)
Having and mastering the correct grammar in written even spoken English is considered as one of the major aspects needed in basic communication or delivering each other’s means. Therefore, this research is done in purpose of finding what are the most often grammatical mistakes that happened while communicating in English. But while working on this research, we, as a group, decided to set up a barometer, that the search and observation will only take focus on spoken English grammar, which is considered as nowadays underestimated factor in delivering proper English in daily life. Mostly by non-native speakers. We implement this research to 10 random students in UIB, give out a simple question, then through their answers we analyse the grammatical errors that we'll possibly find. And lastly draw conclusion from what we can get.